PENDUGAAN POTENSI DAN PEMANFAATAN SUMBER DAYA AIR SUB DAS BATANG MASUMAI KABUPATEN MERANGIN (Studi Kasus Pada Taman Nasional Kerinci Seblat) - , Agusman, Prof. Dr. Ir. Djoko Marsono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Kerinci Seblat National Park is one of important catchment areas of the river flow areas in 4 provinces. One of them is the Batang Masumai Watershed of Merangin district. It was assumed that the disturbance threat of the area and the use of the land would influence the water supply of Batang Masumai watershed. The study aimed at appraising the water potential of the Kerinci Seblat National Park area, the need of the people Pangkalan Jambu subdistrict for water and at finding out water critical index in the Pangkalan Jambu subdistrict of Batang Masumai watershed. The water potential was calculated using Mock's method (1973). The input data were half-month rainfall, atmospheric moisture, wind speed, sun light exposure duration, daily temperature and observed debit. The data was used to calculate the magnitude of evaporation in addition to parameter optimizing to determine the water flow debit. Calibration and verification were conducted to find out the accuracy of the model for the parameters by considering the correlation coefficient (R) â¥ 70%, volume error (VE) â¤ 5% and standard error (SE) < 0,8. A weighing was conducted to find out the magnitude of the flow debit potential of the Kerinci Seblat national park, while the need of Pangkalan Jambu subdistrict for water was calculated using the approach of the water use resulting from the study by the Research and Development Division of the Department of Public Work. The results of the study showed that the average water potential of the Batang Masumai watershed in 2000-2009 was predicted to be 7.05 m3/second, while the average potential of the water resource of the national park was predicted to be 4.07 m3/second (128,385,877.21 m3/year). The total need of Pangkalan Jambu subdistrict for water was 1,435,509.36 m3/year with the average predicted need of 0.944 m3/second. The highest need took place at the beginning of March and September, which was 1.54 m3/second. The water critical index based on the average water potential and the need of the water indicated the situation close to a critical condition in September and the remaining time has not been critical.